(untitled) (UNWE Yearbook, 2007)
Bulgarian higher education is undergoing a process of dynamic change due to a number of reasons of both more general and more specific nature. The quality and effectiveness of the process of education as coordinates of its competitiveness represent the underlying structural areas of the academic reform. This makes it imperative to acquire familiarity with the competitive environment of higher education and the entrepreneurial type of management with regard to its competitive factors, including those described as extensively integral: i.e. private institutions of higher learning and foreign subsidiaries offering higher education.